MAYER-ROKITANSKY-KUSTER-HAUSER SYNDROME (CLINICAL CASE) - Марина Анатольевна Ющенко; Алена Викторовна Робул; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Анна Александровна Железная; Полина Никитична Мраморнова; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2022)
The Mayer-Rokitansky-Custer-Hauser syndrome (SMRCX) is a violation of the intrauterine development of the Pmuller ducts, leading to aplasia of the vagina and uterus. It is diagnosed in 1 out of 4500-5000 newborn girls. The etiology of the syndrome has not been sufficiently studied. According to world statistics, the role of hereditary factors in the formation of malformations of the reproductive system ranges from 10 to 25 %. This article describes a rare clinical case of MRC syndrome. Considering the optimal chosen management tactics of the patient, a favorable outcome was obtained for the woman.